PENGARUH MODEL PEMBELAJARAN POE BERPENDEKATAN STEAM TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA - Anggraini, Yunita Mahbubah; Wahyuni, Eva Ari; Sidik, Rahmad Fajar; Rakhmawan, Aditya; Hadi, Wiwin Puspita (Program Studi Pendidikan IPA, Universitas Trunojoyo Madura, 2023)
This aims of this research to know the effect of the STEAM approach POE learning model on students critical thinking skills. The material used in this research is the excreting system in humans. This research is a type of quantitative research using experimental methods. The POE learning model consist of 3 stages, namely predicting, observing and explaning. The approach taken in the learning uses STEAM which includes knowledge, technology, methods, art, and mathematics. The research population is class VIII MTs Al Karimi 1 Gresik for the academic year 2021/2022. The research population sample was class VIII A as the axperimental class and VIII B as the control class. The research instrument that was validated got a value of more than 0.75 with a very valid category. Student responses to the POE learning model with the STEAM approach obtained an average percentage of 91.84% which was categorized as very good. The result ahowed that the pre test score was 61.63 in the experimental class and 61.67 in the control class. Meanwhile, at the post test the experimental class scored 86.58 and the control class 7633. It can be concluded that there is a significant effect of using the STEAM approach to the POE learning model on student’s critical thinking skills.